A Needs Analysis for the Development of E-Comic Media Based on the Local Wisdom of Sidoarjo’s Traditional Foods for Elementary School Students - Prihantini, Mudhachiroh Henik; Istiq’faroh, Nurul; Sukartiningsih, Wahyu; Mariana, Neni; Muhimmah, Hitta Alfi (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to analyze the need for developing e-comic learning media based on the local wisdom of traditional Sidoarjo cuisine for elementary school students. The motivation for this research arises from the limited use of interactive and contextual learning media in primary schools. A qualitative descriptive approach was employed, utilizing data collection methods such as observation, interviews, and questionnaires involving students, teachers, and school principals. The results indicate that 86% of students prefer digital media, while 77% enjoy illustrated storytelling formats. Furthermore, the majority of students have a limited understanding of their local traditional cuisine. Teachers and school principals expressed strong support for the development of e-comic media with local content, viewing it as both relevant and engaging for students. This study recommends the creation of e-comic media that not only enhances learning motivation but also fosters an appreciation for local culture.